2013
DOI: 10.1155/2013/658939
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structure, and Characterization of a New Organic-Inorganic Hybrid Material:

Abstract: The title compound is an organic-inorganic hybrid material. The single crystal X-ray diffraction investigation reveals that the studied compound crystallizes in the orthorhombic system, space group Pbca with the following lattice parameters:  (4) Å,  (3) Å,  (6) Å, and . The crystal lattice is composed of a discrete anion surrounded by piperazinium cations, chlorine anions, and water molecules. Complex hydrogen bonding interactions between , , organic cations, and water molecules form a three-dimensional netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…The obtained spectra are shown in Fig. 7, indicating that the (C 6 N 2 H 7 S) 2 [SbCl 4 ]Cl exhibits two distinct absorption bands around 4.01 eV (310 nm) and 4.36 eV (285 nm) which are attributed to the metal charge transfer (LMCT) transition from the 3p orbital of Cl to 5p orbital of Sb(III) as described in previous outputs [35,[37][38][39]. On the other hand, the photoluminescence spectrum Fig.…”
Section: Optical Studysupporting
confidence: 52%
See 3 more Smart Citations
“…The obtained spectra are shown in Fig. 7, indicating that the (C 6 N 2 H 7 S) 2 [SbCl 4 ]Cl exhibits two distinct absorption bands around 4.01 eV (310 nm) and 4.36 eV (285 nm) which are attributed to the metal charge transfer (LMCT) transition from the 3p orbital of Cl to 5p orbital of Sb(III) as described in previous outputs [35,[37][38][39]. On the other hand, the photoluminescence spectrum Fig.…”
Section: Optical Studysupporting
confidence: 52%
“…According to some studies reported in the literature [2,[27][28][29][30][31][32][33][34][35] we can propose an attempt of assignment of the observed bands Table 3.…”
Section: Infrared Spectroscopymentioning
confidence: 97%
See 2 more Smart Citations
“…32,35,39 For example, for a series of compounds containing , and BiI 6 3-anions, the lowest energy spectral feature assigned as LMCT is present at 231 nm (X = Cl) vs. 274 nm (X = Br) vs. 412 nm (X = I). 40 Thus, under the standard conditions of our aerobic synthesis, it can be inferred that iodide anions are complexed with the Bi 3+ ions until reduction and behave as non-innocent ligands in the reduction of Bi 3+ to form Bi NPs.…”
Section: Investigation Of the Mechanism Of Bi Np Formationmentioning
confidence: 99%